2016
DOI: 10.1007/s12155-016-9763-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency for Sugarcane-Biofuel Production: What Is Next?

Abstract: Land area devoted to sugarcane (Saccharum spp.) production in Brazil has increased from 2 million to 10 million ha over the past four decades. Studies have shown that, from an environmental perspective, the transformation of nitrogen (N) fertilizers into N 2 O gases can offset the advantages gained by replacing fossil fuels with biofuels. Our objectives here were to review recent developments in N management for sugarcane-biofuel production and assess estimates of N use efficiency (NUE) and N losses based on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 128 publications
5
75
1
20
Order By: Relevance
“…Multiple recent studies have shown that temperate perennial bioenergy crops only reduce measured GHG emission compared to annuals if they are not fertilized [34,43,44]. In Brazil, maintaining N amendment rates and improving nitrogen use efficiency (NUE) through genetic improvement and better management practices are critical to increasing biofuel production sustainably [45]. In these Brazilian systems, N losses to leaching and N 2 O emission can be as high as 5.6% of added N. In this study, gaseous losses were consistently very low because of efficient fertilizer and irrigation practices in use on the plantation.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple recent studies have shown that temperate perennial bioenergy crops only reduce measured GHG emission compared to annuals if they are not fertilized [34,43,44]. In Brazil, maintaining N amendment rates and improving nitrogen use efficiency (NUE) through genetic improvement and better management practices are critical to increasing biofuel production sustainably [45]. In these Brazilian systems, N losses to leaching and N 2 O emission can be as high as 5.6% of added N. In this study, gaseous losses were consistently very low because of efficient fertilizer and irrigation practices in use on the plantation.…”
Section: Resultsmentioning
confidence: 99%
“…This trend was not observed for P, Ca, and Mg (Table 4). The efficiency of N fertilizer uptake by sugarcane was approximately 49% when the equivalent to 100 kg N•ha −1 was applied (Table 5), and this value was well above the range of 5 to 30% reported for the crop in other regions (Meier et al 2006;Trivelin et al 1996;Franco et al 2011;Otto et al 2016). The lowest efficiencies of N acquisition by sugarcane can be a consequence of N source and rainfall, when there is no other apparent limitation for the plant growth.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 54%
“…Nitrogen is usually a limiting nutrient to crop yield in the weathered tropical soils, and positive yield responses to N fertilization are observed for sugarcane in Brazil (Dourado Neto et al 2010;Fortes et al 2013), although less frequently to plant cane (first cycle) owing to higher contribution from N in soil and residue due to N mineralization, as well as the biological nitrogen fixation (Balasubramanian et al 2004;Urquiaga et al 2012;Otto et al 2016). A review on sugarcane pointed out the relatively low N use efficiency (NUE) by the crop, which averages 26% from a range of 7 to 40% of the N fertilizer applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). In comparison, a yield reduction in sugarcane is commonly observed in later crop cycles (Dharmawardene, 2005;Matsuoka and Stolf, 2012;Otto et al, 2016;Castro et al, 2017) than a yield increase, mainly due to the lack of traffic control during mechanized harvesting (Camilotti et al, 2005;Tavares et Magalhães et al, 2012;Cassia et al, 2014) that can cause damage in ratoon cycles, thus reducing plant density. In comparison, a yield reduction in sugarcane is commonly observed in later crop cycles (Dharmawardene, 2005;Matsuoka and Stolf, 2012;Otto et al, 2016;Castro et al, 2017) than a yield increase, mainly due to the lack of traffic control during mechanized harvesting (Camilotti et al, 2005;Tavares et Magalhães et al, 2012;Cassia et al, 2014) that can cause damage in ratoon cycles, thus reducing plant density.…”
Section: Discussion Biomass Production and Juice Qualitymentioning
confidence: 99%